ECAR Study of Students and Information Technology, 2014 (Educause Center for Applied Research (ECAR))
In 2014, ECAR also collaborated with 213 institutions to collect responses from 75,306 undergraduate students about their technology experiences.

(untitled) - Dahlstrom, Eden; Bichsel, Jacqueline (2014)